A new hybrid LED driver - Sagi, Orazbayev; Erlan, Dzhunusbekov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The ongoing challenge in light-emitting diode (LED) lighting is to integrate power and control circuits into a single chip to reduce the number and cost of components, minimize size, and enhance reliability. This integration requires a reduction in power dissipation on the chip, improved efficiency, and smaller magnetic components. Recently, hybrid LED drivers have been proposed to address this integration challenge. Unlike traditional transformerless single-stage LED drivers, which implement boost or buck topologies, hybrid drivers reduce pulsed voltage on power semiconductors. The proposed hybrid LED driver aims to prevent power switches from hard switching, which in turn reduces metal–oxide semiconductor field-effect transistor or MOSFETs' overheating in the integrated circuit body, increases the reliability of the chip, and alleviates electromagnetic interference or EMI issues. The proposed improvement to the hybrid driver is analyzed. The control method was suggested. Computer modelling was provided to confirm the feasibility, controllability and resulting advantages of the proposal. The proposed hybrid LED driver is attractive for circuit integration to reduce size and cost compared to the achievements of previous art.